2022
DOI: 10.1007/s11240-022-02348-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and endogenous phytohormone changes during long-term embryogenic cultures in Korean pine

Abstract: Somatic embryogenesis (SE) is a biotechnological tool with high application potential for in vitro propagation and regeneration of conifers species. However, in SE of Korean pine, a dominant species of the natural mixed coniferous and broadleaf forests of the temperate forests in Northeast China, decreasing embryogenic potential was found in embryogenic callus (EC) with successive subcultures, especially when the cultures were maintained for more than 5-6 months, which is one of the most signi cant problems pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The results are in agreement with the results reported by Liang et al [29], who found that considerable differences in endogenous hormone levels were measured between normal and abnormal types of embryos in grapevine (Vitis vinifera). Similar results were also obtained in Pinus koraien, and substantial changes in endogenous hormones were found among the different types of calli [28].…”
Section: Differences In the Endogenous Hormone Content And Antioxidan...supporting
confidence: 83%
See 2 more Smart Citations
“…The results are in agreement with the results reported by Liang et al [29], who found that considerable differences in endogenous hormone levels were measured between normal and abnormal types of embryos in grapevine (Vitis vinifera). Similar results were also obtained in Pinus koraien, and substantial changes in endogenous hormones were found among the different types of calli [28].…”
Section: Differences In the Endogenous Hormone Content And Antioxidan...supporting
confidence: 83%
“…Auxins, cytokinins, gibberellins, abscisic acid, and ethylene are commonly considered to be the main natural plant hormones. Recently, the effects of the endogenous hormone content on in vitro culture responses have been studied in a variety of plant species, such as Tulbaghia simmleri [27], Pinus koraiensis [28], and Vitis vinifera [29]. The morphogenetic abilities are different in different explant types, which may be attributed to the differences in their endogenous hormone content [28,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been different theories on the possible mechanisms associated with the loss of yield in the maturation phase, in addition to the damage that could be generated because of handling during subculturing. Although, in some species, ET can multiply in culture media free of PGRs [50], the vast majority require a complex network of interactions between endogenous and exogenous PGRs, mainly auxins and cytokinins, during the early pro-embryogenic stages and ethylene, gibberellic, and abscisic acids later in the development of Se [11,51,52]. Therefore, prolonged exposure to these regulators, mainly 2.4-D auxin, could generate an imbalance in their transport or synthesis, which could cause problems in the following stages [14,19,53].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of various types of endogenous hormones collaborated in the formation of potential embryoids. The high content of ABA helped in embryo differentiation, while the addition of low IAA and zeatin maintained the embryogenic potential in Korean pine callus (Liang et al, 2022). The content of endogenous hormones ABA, IAA, and GA 3 in Ormosia henryi Prain.…”
Section: Effect Of Endogenous Hormones On Embryoid Inductionmentioning
confidence: 93%